Formulasi dan Uji Stabilitas Fisik Sediaan Lulur Krim Ekstrak Daun Pandan Wangi (Pandanus amaryllifolius Roxb.) - Zuhairiah Nasution; Mutiara Agustina Nst; Puput Fransiska Hareva (Program Studi S1 Farmasi, STIKES Senior, Medan, 2022)
Scrub cream is a pharmaceutical preparation which function is to remove dead skin cells, moisturize and brighten the skin with the help of scrub ingredients. One of the natural ingredients used as raw material for scrub cream is fragrant pandan (Pandanus amaryllifolius Roxb.). The aim of this study was to make a cream scrub preparation from pandan extract with various concentrations of 3%, 3.5% and 4%. This research was conducted experimentally. Preparation testing includes organoleptic test, homogeneity test, pH test, irritation test, spreadability test, stability test, and emulsion type test. The results of the physical quality inspection of the scrub cream from pandan Wangi extract showed that the preparation was homogeneous, had an M/A emulsion type, had a pH value of 6.1-6.5, did not cause irritation and did not change during storage for 4 weeks except for the preparation with a concentration of 3.5% because the preparation underwent a change in the breakdown of the emulsion in the preparation on storage starting from the 3rd week. From the research that has been done, it can be concluded that Pandanus amaryllifolius Roxb extract can be formulated as a scrub cream with a variation of concentration of 3%; 3.5% and 4% and does not irritate the volunteers' skin.